Dynamics Post-Hizb ut-Tahrir Indonesia (HTI) Dissolution: Activist Reactions and Public Response - Ma'mur, Ilzamudin; Hidayani, Selnistia; M. Luthfi,; Mubarok, Mochamad Gilang Ardela (International Journal of Islamic Khazanah, 2025)
This study examines the complex responses to the dissolution of Hizb ut-Tahrir Indonesia (HTI), a pro-Caliphate organization, by the Indonesian government in 2017. The primary objective is to comprehensively analyze the dynamics of these responses from activists, sympathizers, and the general public. Employing a qualitative descriptive-sociological methodology with a case study approach, this research collected data through a literature review, observation, interviews, and documentation in West Java, Banten, and Jakarta. The dissolution, initiated via Perppu No. 2 of 2017, triggered diverse reactions and polarized public opinion, reflecting a broader societal rejection of the Caliphate ideology. Importantly, the study found that HTI's movement did not cease but evolved. Post-dissolution strategies include leveraging social media for discourse and issue manipulation, infiltrating other socio-political organizations, and utilizing digital platforms for clandestine cadre regeneration, particularly among university students. This research provides a comprehensive understanding of HTI's post-dissolution dynamics, contributing significantly to the literature on social movements by demonstrating movement resilience and authoritarian learning—the organization's adaptation from a public, confrontational entity to a hidden, digitally-enabled movement in response to state repression. The findings have crucial implications for deradicalization policies and highlight the intricate socio-political responses to state action against ideological groups.